Effect of Matricaria recutita Ointment on Coronary Artery Bypass Graft (CABG) Wound Healing in Diabetic Patients at Imam Ali Hospital in Kermanshah - soraya nejati; keivan babaei; shokoh varaei; reza hajiaghaei; anoshirvan kazem nezhad (Institue of Medicinal Plants, ACECR, 2019)
Background: One of the complications of diabetes is delayed wound healing. One of the common treatments for diabetic patients with coronary artery bypass graft surgery is coronary artery bypass surgery. Objective: Regarding the healing effects of chamomile on wounds, a study was conducted to determine the effect of Matricaria recutita on coronary artery bypass graft surgery in diabetic patients. Method: This is a quasi-experimental study with control group. 60 diabetic patients referred to coronary artery bypass graft surgery were randomly divided into two groups of 30 intervention and control groups. From the second day after surgery, after removal of the endotracheal tube, the wound area of the patients in the intervention group was washed daily with betadine and dressed with M. recutita ointment. In the control group, only washing with betadine and dressing was performed. Intervention was performed up to 14 days after surgery. Wound healing was assessed on days 4, 7 and 14 postoperatively by the Bates-jensen scale. Results: The two groups were homogeneous in terms of demographic characteristics. The mean and standard deviation of the wound healing score between the two groups was calculated on the fourth days after the intervention (P = 0.75). There was no significant difference between the two groups on the fourth day after surgery, but 7 days after the intervention there was a significant difference in the mean and standard deviation of wound healing in both groups. Also 14 days after the intervention, there was a significant difference between the two groups with the Mann-Whitney U test (P = 0.002). Conclusion: Chamomile ointment after at least one week of use can accelerate healing of coronary artery bypass graft surgery in diabetic patients.